The Effectiveness of IEC Using Booklet and Video Media on Diarrhea Prevention Efforts on the Knowledge of Posyandu Cadres - Nuke Indrawati; Nurul Aryastuti; Fitri Ekasari; Nova Muhani (Jurnal Penelitian Pendidikan IPA, 2023)
Diarrhea is still the most common cause of death in the post-neonatal period, which is 14% of deaths due to diarrhea. Success in preventing children from getting into more severe conditions due to diarrhea cannot be separated from the role of posyandu cadres. Efforts to increase the knowledge of cadres about diarrhea prevention is health education. This study aimed to determine the effectiveness of KIE using booklet media and videos about efforts to prevent diarrhea on the knowledge of posyandu cadres at the Gunung Sugih Community Health Center, Central Lampung Regency, in 2023. This type of research is quantitative research using a quasi-experimental design and a pretest-posttest design with a control group. The population in this study were all cadres at the Gunung Sugih Health Center with a total of 50 people with a sampling technique using total sampling. The intervention group was given CIE using a booklet, and the control group was assigned CIE using a video. Data analysis in this study used univariate and Mann-Whitney. The results of this study indicate that the average knowledge before being given health education using booklet media is 57.52, and after being given health education is 91.48. While the intermediate knowledge before being given health education using video media was 58.60, and after being given health education was 93.56. Based on the results of the Mann-Whitney test, it was found that the p-value was 0.625 > 0.05, meaning that there was no difference in the effectiveness of KIE using booklets and videos on diarrhea prevention efforts on the knowledge of posyandu cadres at the Gunung Sugih Health Center, Central Lampung Regency in 2023. Suggestions for cadres after being given education This health service can pass on information to mothers with toddlers.